Wacana Intelektual Muslim Indonesiatentang Kompatibilitas Islam Dengan Demokrasi - Winengan Winengan (Universitas Islam Negeri Mataram, 2005)
In the beginning era of Islam, contextual and highly abstract terms like democracy was unknown. Therefore, when the term exists and is applied in the context of muslims’ states, it is responded in various ways due to some reasons. First, respond under genealogical reasons that assumes that democracy was first applied in the Western countries as a product of secular and liberal thinking process. Second, respond under philosophical reasons which looks at democracy through its political aspect that is closely related to state power in which people are found as the source of the power. In the meantime, as for a muslims, the dignity of power is in the Hand of Allah, the Creator. The problem arouses due to the application of democracy in Islam interest some Indonesian Moslem scholars. By using Islamic teaching value study approaches, this article is aimed at describing their opinions about the meaning of term democracy. Among them are M. Amien Rais, Nurcholish Madjid, Ismail Sunny, Syafi’i Ma’arif, Abdoerraoef, Jalaluddin Rakhmat, Muhammad Natsir, Muhammad Tahir Azhary, M. Dawam Rahardjo, Abdurrahman Wahid, and Munawir Sadzali. Based on their point of views, it seems that they do not question the meaning of democracy genealogically. They agree, even, support the concept of democracy which is understood contemporarily, in terms of the power of majority, people’s voice (political participations), and free and responsible election. About the philosophical definition, although they accept the concept of people power, they still perceive the supremacy of God’s order (Syariah) as the basis and is treated as the highest source of power.